PERAN PEMERINTAH DALAM PENGELOLAAN PELABUHAN KALIMAS SURABAYA DALAM PERSPEKTIF PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA NOMOR PM 146 TAHUN 2016 - Imam Teguh Santoso & Achmad Syafii (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
In accordance with Peraturan Kepala Kantor Otoritas Pelabuhan III Tanjung Perak Nomor: HK: 208/01/04/OP.TPr-12, concerning Systems and Procedures for Ship and Goods Services in Kalimas Terminal Article 2, Kalimas Terminal Pier is only for ships carrying out activities loading and unloading of goods. With the provisions, the type of KM (Motor Boat) with a maximum overall length of 55 meters, KLM (Motorcycle Sailing Boat), PLM (Motorcycle Sailboats) and traditional ships. This regulation is strengthened by Surat Edaran Nomor: 11M-003/13/19/Syb.TPr-13, concerning Safety, Order and Smoothness of Ship Traffic at Kalimas Pier, Tanjung Perak. Traditional ships, KLM/PLM and KM alone can be in Pelra Kalimas. That, too, is only allowed to load and unload, if not have to exit. It turned out that a large ship with a cargo capacity of 1,000 tons-3,000 tons entered and filled Kalimas. Because at this time the water is receding, the large KM cannot get out of Kalimas. Its presence as well as close the traffic of small ships. Large vessels meet at Pos 1-3, while traditional vessels, KLM/PLM are 'isolated' at posts 4-5. On the other hand, the Policy of the Peraturan Menteri Perhubungan Republik Indonesia Nomor: PM 146 of 2016 has governed all the provisions of the Operation of the Seaport including the Surabaya Kalimas Port. Research with this qualitative method found that the implementation of the policy was going quite well but there were still some obstacles in the operation of the port of Kalimas.